2009
DOI: 10.1093/carcin/bgp250
|View full text |Cite
|
Sign up to set email alerts
|

miR-124 and miR-203 are epigenetically silenced tumor-suppressive microRNAs in hepatocellular carcinoma

Abstract: MicroRNAs (miRNAs) are a class of small non-coding RNAs that, in general, negatively regulate gene expression. They have been identified in various tumor types, showing that different sets of miRNAs are usually deregulated in different cancers. Some miRNA genes harboring CpG islands undergo methylation-mediated silencing, a characteristic of many tumor suppressor genes. To identify such miRNAs in hepatocellular carcinoma (HCC), we first examined the methylation status of 43 loci containing CpG islands around 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
422
2
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 533 publications
(459 citation statements)
references
References 42 publications
31
422
2
4
Order By: Relevance
“…The current authors previously reported that the miR-124 expression was down-regulated in cutaneous SCC (14), which results in the overexpression of ERK as a target molecule and subsequent cell proliferation. miR-124 was also reported to be involved in the carcinogenesis of various cancers such as glioblastoma, gastric cancer, hepatocellular cancer, breast cancer, and prostate cancer (15)(16)(17)(18)(19), indicating that miR-124 is a key miRNA in carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…The current authors previously reported that the miR-124 expression was down-regulated in cutaneous SCC (14), which results in the overexpression of ERK as a target molecule and subsequent cell proliferation. miR-124 was also reported to be involved in the carcinogenesis of various cancers such as glioblastoma, gastric cancer, hepatocellular cancer, breast cancer, and prostate cancer (15)(16)(17)(18)(19), indicating that miR-124 is a key miRNA in carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, using regioneR (48), which assesses the relation between genomic regions using a permutation test, we observed that a higher proportion of miRNA genes than expected by chance is embedded in CpG islands susceptible to methylation (189 of 1881; z-score = 46.13; number of permutations = 1000; p-value = 0.0009, Figure 1B and C, Table 1 and shown in red in Figure 1A), which might explain why certain miRNAs are more prone to be epigenetically regulated by methylation than others. Furuta et al (49) studied the methylation grade of CpG islands close to 39 miRNA genes in hepatocellular carcinoma cell lines and found that miR-124-1, miR-124-3, miR-203 and miR-375, which were completely embedded in a CpG island, underwent methylation-mediated silencing ( Figure 2A). miRNAs can be classified into two broad categories according to their genomic region: intergenic and intragenic (50,51).…”
Section: Dna Methylationmentioning
confidence: 99%
“…As shown in previous findings, miRNA levels seem to be lower in tumors than normal tissues. ABCE1 gene has been implied to be a novel possible target for miR-203, inferring that hypermethylationmediated silencing of tumor-suppressive miRNAs induces the increased expression of ABCE1 gene, contributing to the pathogenesis of hepatocellular carcinoma (HCC) (44). RNase L has been shown to have an impact on the pathogenesis of prostate cancer.…”
Section: Abce1 Associates With Tumormentioning
confidence: 99%